Implementasi Bimbingan Kelompok Dengan Teknik Self Management Untuk Meningkatkan Kedisiplinan belajar Siswa Kelas X - Putu Agus Giri; Ega Dwi Meriani; Adjie Achmad Zaini; Arwin Nugraha Pratihara (Journal Prakarsa Paedagogia, 2024)
The lack of students' ability to manage their study time results in low learning discipline. Self-management is part of behavioral techniques to change the behavior of counselees through an approach that helps in managing time effectively. Therefore, the researcher chose this technique for a study aimed at transforming students' behavior from having poor time management to good time management. Based on the research conducted in grade X, it was found that the use of group guidance with a self-management approach was effective in helping students improve their learning discipline. By providing group guidance services, several causes of students' low learning discipline, such as being late to class, reluctance to take notes, not paying attention to the teacher's explanation, causing disturbances in class, and wasting available study time, could be minimized..